USE OF LEARNING MODEL TRUE OR FALSE LEARNING TO IMPROVE RESULTS POLITICAL SYSTEM IN INDONESIA PRODI PPKN FKIP UNIVERSITY RIAU - Erlinda, Sri (Proceeding 7th International Seminar on Regional Education, 2015)
Abstract This research aims to improve, identify and describe the learning outcomes of Indonesian Political System in Prodi PPKn using learning models True or False. The subject of research is the third semester students numbering 36 people composed of 12 men and 14 women. Implementation of the repair process of learning is implemented as two cycles in value by an observer. While the types of data and data collection techniques as follows; faculty and student activity data collected through observation sheet, whereas the results by conducting a test. After the data is collected, then grouped, recently analyzed by descriptive method where the data obtained are given an explanation. The results showed that the application of learning models True or False can improve learning outcomes Indonesia Political System in Prodi PPKn FKIP UNRI.Keywords: true or false, the result of learning